BOOK PROVIDING AND LOAN: BY EXPERIENCE OF THE LIBRARY AT DNIPROPETROVSK NATIONAL UNIVERSITY OF RAILWAY TRANSPORT NAMED AFTER ACADEMICIAN V. LAZARYAN - Petrenko, Olena A.; Slyshchenko, Tetiana A. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The paper highlights the processes of library bibliographic activity at Dnipropetrovsk National University of Railway Transport named after Academician V. Lazaryan (DNURT). Special attention is directed to the acquisition, book providing and automated loan.